Home-based work in Victorian Britain - Joseph, Gillian, author.
1 online resource
Keywords: "Home-based work has increased in recent decades and intensified as a result of policies created to control the spread of Covid-19, creating a labour market in rapid transition. Yet little attention has been paid to the issues associated with occupational health and safety or to how employers will monitor and maintain employee health and safety in a home-based work environment. Using historical case studies from Victorian Britain, this book reflects on the past to examine resurfacing health and safety concerns that shaped, and continue to shape, the home-based working experience. Anchored by family research case studies, this book presents documents and newspaper accounts about the diverse experiences of three real people who lived and worked from their homes in the Victorian era. Supported by academic and popular literature on work and policy about the era, the book discusses changing worldviews and social context that shaped occupational health and safety at the time and critiques the outcomes of policies that were challenged to address these risks. The case study experiences are used as a touchstone between the past and present to draw parallels between important health and safety concerns that may be resurfacing in our modern post-COVID transition to home-based work. This book will be a valuable resource for researchers, academics and postgraduate students of occupational health and safety, occupational science, labour history, and human resource management, as well as Victorian studies. It will also be of interest to policy makers and practitioners working across the fields of workplace and occupational health and safety"--